2001
DOI: 10.1002/1521-379x(200106)53:6<269::aid-star269>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Supramolecular Structures of Aroma Compounds with Polysaccharides of Corn Starch Cryotextures

Abstract: Starch/Stärke 53 (2001) 269-277 269 Research PaperThe binding absorption of individual alcohols, ketones, alkyl acetates and their mixtures -used as aroma compounds -from aqueous solutions by corn starch cryotextures was studied by capillary gas chromatography at different starting concentrations of the odourants (1-25 mmol/L). The amount of compound sorbed by the cryotextures increases with concentration of this compound in the initial sol and increasing length of the alkyl chain in the corresponding compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The chemical binding of volatiles by hydrocolloids can also decrease flavor release. The hydrophobic and hydrophilic moieties in hydrocolloids can interact with volatiles (Golovnya, Terenina, Krikunova, Yuryev, & Misharina, 2001). The triple helical structure in gelatin can have cross-linking and three-dimensional network formation, which entraps volatiles.…”
mentioning
confidence: 99%
“…The chemical binding of volatiles by hydrocolloids can also decrease flavor release. The hydrophobic and hydrophilic moieties in hydrocolloids can interact with volatiles (Golovnya, Terenina, Krikunova, Yuryev, & Misharina, 2001). The triple helical structure in gelatin can have cross-linking and three-dimensional network formation, which entraps volatiles.…”
mentioning
confidence: 99%
“…Literature data also pointed out that the physical treatment of starch (drying, freezing carbohydrate sols) may influence the binding properties of starch (Golovnya, Terenina, Krikunova, Yuryev, & Misharina, 2001;Polaczek et al, 1999;Terenina, Krikunova, Medvedeva, & Misharina, 2003). The binding of some alcohols from aqueous solution by maize starch cryotextures was studied by Golovnya et al (2001).…”
Section: Introductionmentioning
confidence: 99%
“…The binding of some alcohols from aqueous solution by maize starch cryotextures was studied by Golovnya et al (2001). These authors showed increased sorption of the aroma compounds by cryotextures.…”
Section: Introductionmentioning
confidence: 99%
“…Retention of volatile organic compounds by starches is related to capillary and surface sorption and formation of hydrogen bonds and inclusion complexes with amylose [1 − 10] or amylopectin [2,4,5,11]. The degree of sorption depends on the physicochemical properties of volatile compounds and sorbent.We previously studied the sorption of organic compounds by cryotextured cornstarches obtained after freezing and defrosting of thermotropic gels [10][11][12][13][14][15]. The study compounds were capable of forming supramolecular complexes with cornstarch polysaccharides, due to hydrophobic cooperative interactions.…”
mentioning
confidence: 99%
“…We previously studied the sorption of organic compounds by cryotextured cornstarches obtained after freezing and defrosting of thermotropic gels [10][11][12][13][14][15]. The study compounds were capable of forming supramolecular complexes with cornstarch polysaccharides, due to hydrophobic cooperative interactions.…”
mentioning
confidence: 99%